2023
DOI: 10.1007/s00330-023-09963-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting visual recovery in pituitary adenoma patients post-endoscopic endonasal transsphenoidal surgery: Harnessing delta-radiomics of the optic chiasm from MRI

Abstract: Objectives To investigate whether morphological changes after surgery and delta-radiomics of the optic chiasm obtained from routine MRI could help predict postoperative visual recovery of pituitary adenoma patients. Methods A total of 130 pituitary adenoma patients were retrospectively enrolled and divided into the recovery group (n = 87) and non-recovery group (n = 43) according to visual outcome 1 year after endoscopic endonasal transsphenoidal surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…More recently Zhang et al reported no correlation between postoperative chiasm morphology and improvement in VF de cits. [24] However, in this study postoperative imaging was performed <72 hours after surgery which is probably an inadequate time-frame for any meaningful change in chiasm dimensions, especially in patients with chronic visual compression from a suprasellar mass. It may appear counter-intuitive that postoperative optic nerve deviations correlated with VF scores and not VA scores in our study.…”
Section: Discussionmentioning
confidence: 93%
“…More recently Zhang et al reported no correlation between postoperative chiasm morphology and improvement in VF de cits. [24] However, in this study postoperative imaging was performed <72 hours after surgery which is probably an inadequate time-frame for any meaningful change in chiasm dimensions, especially in patients with chronic visual compression from a suprasellar mass. It may appear counter-intuitive that postoperative optic nerve deviations correlated with VF scores and not VA scores in our study.…”
Section: Discussionmentioning
confidence: 93%
“…It is the endoscopic skull-base surgery that has been reported to be the best option for visual recovery [44]. Predicting visual acuity and visual field outcomes after removal of chiasmal-sellar tumors is still an important task [107,108,109,110].…”
Section: сHiasmal Syndromementioning
confidence: 99%